Anaesthetic considerations for whole lung lavage for pulmonary alveolar proteinosis - Pandit, Anuja (Ghana Med J, 2019)
Pulmonary alveolar proteinosis (PAP) is an uncommon lung disease characterized by excessive accumulation of pulmonary surfactant that usually requires treatment with whole-lung lavage. A 47-year-old female presented with history of dry cough and breathlessness for past 6months. Chest radiograph demonstrated bilateral alveolar shadows and high resolution computerized tomography thorax showed crazy paving pattern. Broncho-alveolar lavage (BAL) and transbronchial lung biopsy confirmed a diagnosis of PAP. Due to worsening hypoxemia and respiratory failure, wholelung lavage was planned and performed. Anaesthetic management involved integrated use of pre-oxygenation, complete lung isolation, one-lung ventilation with optimal positive end-expiratory pressure, vigilant use of positional manoeuvres, and use of recruitment manoeuvres for the lavaged lung. We have discussed valuable strategies for the anaesthetic management of patients undergoing this multifaceted procedure in a case of severe PAP. FUNDING: None declared